Development of an Interprofessional Small Bowel Placement Training Program - A. Fitzpatrick; M. Houser; C. Fackler; A. Patton; K. Roberts (Journal of the Academy of Nutrition and Dietetics, 2023)

Toward a Resilience-Based Conservation Strategy for Wetlands in Puerto Rico: Meeting Challenges Posed by Environmental Change - Jaime A. Collazo; Adam J. Terando; Augustin C. Engman; Paul F. Fackler; Thomas J. Kwak (Wetlands, 2019)

Structured decision making as a proactive approach to dealing with sea level rise in Florida - Julien Martin; Paul L. Fackler; James D. Nichols; Bruce C. Lubow; Mitchell J. Eaton; Michael C. Runge; Bradley M. Stith; Catherine A. Langtimm (Climatic Change, 2011)

An Adaptive‐Management Framework for Optimal Control of Hiking Near Golden Eagle Nests in Denali National Park - JULIEN MARTIN; PAUL L. FACKLER; JAMES D. NICHOLS; MICHAEL C. RUNGE; CAROL L. McINTYRE; BRUCE L. LUBOW; MAGGIE C. McCLUSKIE; JOEL A. SCHMUTZ (Conservation Biology, 2011)
Unintended effects of recreational activities in protected areas are of growing concern. We used an adaptive‐management framework to develop guidelines for optimally managing hiking activities to maintain desired levels of territory occupancy and reproductive success of Golden Eagles (Aquila chrysaetos) in Denali National Park (Alaska, U.S.A.). The management decision was to restrict human access (hikers) to particular nesting territories to reduce disturbance. The management objective was to minimize restrictions on hikers while maintaining reproductive performance of eagles above some specified level. We based our decision analysis on predictive models of site occupancy of eagles developed using a combination of expert opinion and data collected from 93 eagle territories over 20 years. The best predictive model showed that restricting human access to eagle territories had little effect on occupancy dynamics. However, when considering important sources of uncertainty in the models, including environmental stochasticity, imperfect detection of hares on which eagles prey, and model uncertainty, restricting access of territories to hikers improved eagle reproduction substantially. An adaptive management framework such as ours may help reduce uncertainty of the effects of hiking activities on Golden Eagles.

Integrated Sensing and Processing Acoustic Resonance Spectrometry (ISP-ARS) for Sample Classification - Joseph P. Medendorp; Jason A. Fackler; Craig C. Douglas; Robert A. Lodder (Journal of Pharmaceutical Innovation, 2007)